2019
DOI: 10.1098/rsta.2019.0114
|View full text |Cite
|
Sign up to set email alerts
|

Equilibration of energies in a two-dimensional harmonic graphene lattice

Abstract: We study dynamical phenomena in a harmonic graphene (honeycomb) lattice, consisting of equal particles connected by linear and angular springs. Equations of in-plane motion for the lattice are derived. Initial conditions typical for molecular dynamic modelling are considered. Particles have random initial velocities and zero displacements. In this case, the lattice is far from thermal equilibrium. In particular, initial kinetic and potential energies are not equal. Moreover, initial kinetic energies (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In the present paper, we study an adiabatic non-equilibrium process analogous to those considered previously [22][23][24][25][26][27]. This process is, however, initiated by instantaneous loading instead of instantaneous heating.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present paper, we study an adiabatic non-equilibrium process analogous to those considered previously [22][23][24][25][26][27]. This process is, however, initiated by instantaneous loading instead of instantaneous heating.…”
Section: Introductionmentioning
confidence: 93%
“…In the pioneering paper by Klein and Prigogine [20], the equations of atomic motion for a onedimensional harmonic crystal were solved directly and it was shown that the energy oscillations following an instantaneous thermal perturbation were described by the Bessel function of the first kind. In later work [21], this problem was solved by analysing the dynamics equations of the velocity covariances, which allowed generalization of these results to more complex systems, including multidimensional crystals [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Displacements of atoms from the unit cell {n, m} are denoted as 2D vectors U n,m , V n,m . Following [27], we use the harmonic approximation for the potential energy of the lattice. Each atom is connected with three nearest neighbors by linear springs (bonds) with stiffness c. Additionally, the nearest bonds between particles are connected by angular springs with stiffness g. Equations of motion for this system were obtained using the Euler-Lagrange formalism in paper [27].…”
Section: Equations Of Motion and Initial Conditionsmentioning
confidence: 99%
“…Such crystals support rotobreathers that are dynamical regimes, in which one molecule (or particle) rotates, while others oscillate [ 31 , 32 , 33 , 34 , 35 ]. Properties of graphene can be described using particles with rotational degrees of freedom [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%